P6 Cultural differences in the acceptability of home sampling for HIV infection. (23rd May 2012) - Bowman, C A; Bell, G; Ellam, H; Tunbridge, A; Slack, S; Atkin, A; Evans, C; Shutt, A; Joseph, E; Naylor, S; Herman, S; Green, S; et al.
Abstract : Background: MSM community outreach using oral home sampling kits posted to virology for testing previously demonstrated success in attracting non-healthcare seeking individuals at risk of HIV. The outcome of targeting other specific at-risk groups to offer home sampling has not previously been described. Objective: To determine the acceptability of home sampling kits for HIV using oral swabs in two at-risk groups Black Africans (BA) and partners of HIV positive patients (PPP). Methods: Self-taken oral fluid home sampling kits were returned to virology for testing using two HIV assays: Roche COBAS and Genscreen Ultra (previously validated for oral fluid testing). Total IgG was also measured to assess sample adequacy. Participant recruitment was two-pronged: community based (BA) or via an HIV clinic (PPP). For BA recruitment, home sampling kits were actively promoted at relevant social events and venues by trained African volunteers from July to December 2010. 19 free condom distribution points were also utilised to provide information about HIV and the testing kits. From September to December 2011, PPPs of unknown current HIV status were contacted and offered the option of attending clinic or receiving an oral fluid home sampling kit by post. Results: Despite intense promotional activity, only 12 kits from 11 individuals in the BA community project were returned: 5 male; 6 female. Two of these participants were not African. In the PPP clinic based study, of 46 partners offered a kit, 38 (83%) accepted, and 34 (89%) returned a sample. BA partners were less likely to accept a home sampling kit (9/13; 69%) than white partners (29/33; 88%) in the PPP group. Participant feedback was favourable in both studies. Discussion: Further evaluation is needed to understand the difference in acceptability of this method of HIV testing in specific at-risk groups (MSM, BA and PPP) in community and clinic settings.